1983
DOI: 10.1530/jrf.0.0690555
|View full text |Cite
|
Sign up to set email alerts
|

Variability in different lots of commercial bovine serum albumin affects cell multiplication and hatching of rabbit blastocysts in culture

Abstract: Summary. Rabbit morulae were cultured in vitro for 4 days in a synthetic culture medium supplemented with two different lots of commercial bovine serum albumin (BSA) and two different amino acid formulations in a factorial 2\m=x\2 arrangement. One lot of BSA caused complete hatching of a proportion of blastocysts and formation of more than twice as many cells per blastocyst (hatched and unhatched) as that of the second BSA lot which did not cause complete hatching of any blastocysts. The mean cell numbers of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 8 publications
1
41
0
1
Order By: Relevance
“…Studies with rabbit embryos, however, could not prove this positive effect for all stages or criteria employed (Gulyas et ai, 1969;Manes, 1969;Van Blerkom & Manes, 1974 (Table 4). BSA is known to be contaminated with non-albumin components (Kane & Headon, 1980), varying between lots and resulting in a divergent growth promotion by different lots of commercial BSA (Kane, 1983). In the present study, BSA from more than 2 lots was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with rabbit embryos, however, could not prove this positive effect for all stages or criteria employed (Gulyas et ai, 1969;Manes, 1969;Van Blerkom & Manes, 1974 (Table 4). BSA is known to be contaminated with non-albumin components (Kane & Headon, 1980), varying between lots and resulting in a divergent growth promotion by different lots of commercial BSA (Kane, 1983). In the present study, BSA from more than 2 lots was involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the growth-stimulating factor itself is toxic at levels greater than the optimum. The fact that there is a low molecular-weight growthpromoting factor present as a contaminant in some samples of BSA helps to explain some of the variability associated with the use of BSA as a source of macromolecules for embryo culture (Kane, 1983 …”
Section: Discussionmentioning
confidence: 99%
“…Embryos at the early morula stage were collected from the oviducts of superovulated New Zealand White does 44-48 h after LH injection as described previously (Kane, 1983). Embryos were placed in culture in 0-5 ml droplets of culture medium under paraffin liquid (Merck, Darmstadt, West (Grayson, 1978;Kane, 1983) and cell numbers counted under high power with the aid of an eyepiece micrometer grid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful embryo culture in chemically defined media, as reported in the late 1960s and 1970s, was obtained with media containing serum supplements or bovine serum albumin (BSA). The commercial preparations of BSA frequently used for embryo culture media are relatively impure (Kane and Headon 1980), often containing unknown, low molecular weight proteins, fatty acids, and steroids (Wright and Bondioli 1981), and may vary considerably in their growth-promoting effects (Kane 1983). In fact, a recent study (Kane 1985) reported that the growth-promoting Influence of BSA may be due to a low molecular weight contaminant that can be extracted from BSA.…”
Section: In Vitro Developmentmentioning
confidence: 99%